Phénomènes d’accommodation inter-sujets : le cas des reformulations introduites par OR - Blandine Pennec (Anglophonia)
Communication, whether it is written or oral, cannot be considered as the decoding, by the addressee(s), of messages that have simply been encoded by the speaker. Several factors constitute obstacles and prevent us from adopting such a basic pattern, such as the fact that representations are rarely shared by the speakers, that the latter sometimes use different language registers, and that speech also frequently contains mistakes or lacks adequacy with what the speaker really wants to say. Repairs can be defined as formulations produced afterwards in order to rework a first formulation that they are attached to. They are par excellence devices enabling the speaker to overcome the difficulties evoked above, thus favoring a form of intersubjective accommodation (this concept will be defined throughout the study, and will be contrasted with those of adjustment and readjustment). Repairs fall into two main categories: paraphrastic repairs, when the wording is reworked, and non-paraphrastic repairs, when it is the meaning which is adapted. The coordinating conjunction OR is a prototypical example of polyfunctional marker that can be used as the introducer of a repair, be it paraphrastic or non-paraphrastic. The goal of this study is to understand the compatibility of this marker with the introduction of these two categories of repairs (knowing that OR is also characterized by a large variety of uses, whether metalinguistic or not). Taking as a starting point the fact that a discursive segment is produced with a view to compete with a previous one in the linear order, we will study the interpretative mechanisms as well as the forms of accommodation that result from this pattern.